Andrea Pasta (1706–1782), eclectic scholar of anatomy and clinical medicine, communication and the history of art. (November 2014) - Clerici, Carlo Alfredo; Veneroni, Laura; Patriarca, Carlo
Andrea Pasta was an eclectic visionary light years ahead of his time. He made numerous contributions to the field of medicine, some recognized by his contemporaries and others so visionary that they are being applied only in modern times. His contributions spanned the disciplines of psychology, gynaecology, haematology, infectious diseases and the doctor–patient relationship. Well known among his contemporaries, he combined a passion for clinical medicine and a keen interest in history and art with a strict research methodology and an approach to caring for patients as human beings. By studying his life and works, we can better understand the magnitude and significance of his innovative method and its applicability in modern times and also the significance of his many contributions.